Facile one-pot synthesis of hollow mesoporous fluorescent Gd2O3:Eu/calcium phosphate nanospheres for simultaneous dual-modal imaging and pH-responsive drug delivery. (December 2017) - Lu, Ya-Ru; Gou, Ming-Yu; Zhang, Ling-Yu; Li, Lu; Wang, Ting-ting; Wang, Chun-Gang; Su, Zhong-Min
Abstract: The hollow nanospheres (NSs) composed of lanthanides have become a hot topic owing to their uncommon magnetic and optical properties arising from the 4f electrons. However, only a few novel methods have been developed for effectively integrating small calcium phosphate (CaP) nanoparticles and rare earth oxide drug carriers into an individual hollow mesoporous nanosphere. Herein, we report a facile, reproducible, room-temperature solution method to prepare multifunctional fluorescent hollow mesoporous Gd2 O3 :Eu/CaP (designated as HM-Gd2 O3 :Eu/CaP) NSs by using polyacrylic acid calcium (PAA-Ca) as a template. The excellent luminescent property and obvious T1 -enhancement effect as well as the HM structure endow the HM-Gd2 O3 :Eu/CaP NSs with the capacity of simultaneous dual-modal fluorescence, magnetic resonance (MR) imaging and drug delivery. The nanocontainer-functionality of the HM-Gd2 O3 :Eu/CaP NSs is further validated upon filling with the anti-cancerogenic agent doxorubicin (drug-loading capacity is 749 μg mg −1 ). In addition, the HM-Gd2 O3 :Eu/CaP NSs display excellent pH-responsive and sustained drug release property. In vitro cell cytotoxicity tests verify the HM-Gd2 O3 :Eu/CaP NSs have good biocompatibility when the concentration ≤25 mg mL −1 . Taken together, the results suggested that the HM-Gd2 O3 :Eu/CaP NSs can be applied as fluorescence and MR dual-modal imaging contrast agents and drug delivery vehicles. Graphical abstract: A feasible and effective one-step method was designed by using polyacrylic acid calcium as a template to prepare hollow mosoporous fluorescent Gd2 O3 :Eu/calcium phosphate nanospheres, which possess superior photoluminescence capacity, excellent T1 -weighted MR imaging contrast, good biocompatibility and relatively high doxorubicin payload. Highlights: An effective one-step method was developed to prepare fluorescent hollow mesoporous Gd2 O3 :Eu/calcium phosphate nanospheres. The Gd2 O3 :Eu/calcium phosphate nanospheres exhibit excellent capability in dual-modal imaging as well as drug delivery. The synthetic strategy could be extended to synthesize other kinds of multifunctional composites.